COMMODITIES SPACE FOR SOCIAL INTERACTION IN THE KAMPUNG AROUND CAMPUSES AT JAKARTA - Ramos P Pasaribu; Uras Siahaan; Rumiati Rosaline Tobing (Journal of Architecture&ENVIRONMENT, 2017)
An interesting phenomenon in Indonesia today is that "life coexisting between urban centers with urban village features is another face" (Emil Salim, 1984), things such as those occurring in DKI Jakarta where universities are growing alongside the surrounding kampung.Student activities melt into the kampung to meet their daily needs such as a boarding house (kos-kosan), food, and so on coloring the social interaction space. Not all the kampung that grow together with the surrounding campus have a better change in the space of social interaction. But there are kampungs that experience better economic change which then affect the changes in social interaction space. This study aims to find a kampung in which there is social interaction space in the commodity space dominated by trade homogeneity with the criteria of the settlement of population density > 400 persons/ha has direct achievement from kampung to campus, more kampung formerly existed rather than campus, open kampung type. At a radius of 400 m from the campus there is a building function dominated by trade activities, student activities along the way, and commodification of public open space.Research method using case study, found kampong around the campus where kampung Grogol and Kemanggisan are selected as kampung that has homogeneity of trading activities (commodity space) and heterogenity of college student activities. In it happens the production of (new) social interaction space that produced by the relation between the aspects that effect of commodity space and various of college student activities in kampung.